Taller de Fotografía Periodística - PE66 - 202102 - Caceres Alvarez, Luis Andres (2021)
Description: Taking our present day as context, where images have become the most effective medium of communication, this course has been designed to introduce the student to photojournalism through a hands on approach. This course will give them a general vision of the work as a photojournalist and the options he/she has on the job market. Finalizing the course, the student will be able to work as an independent photojournalist or with different written media such as magazines, newspapers and news agencies. Purpose: This is a specialized course from the career path of Communications and Journalism. It is a theoretical course as well as a hands on course, geared to the students of the sixth semester who wish to develop the general Competences in the Management of Information and innovative thinking. NT: The Photojournalism Workshop has been designed so that the student, through constant hands on practice, will produce portraits, action shots and photo stories which will help her/him develop their capacity to inform and communicate through images an event of public interest in a media of mass communication. This workshops goal is to develop the General Competences of Information Management (level 2)and Innovative Thinking (level 2); and the faculty competence Policy Language (nivel3).